The relationship between Hikikomori risk factors and social withdrawal tendencies among emerging adults—An exploratory study of Hikikomori in Singapore - Lin, Patrick K. F.; Andrew,; Koh, Alethea H. Q.; Liew, Kongmeng (Frontiers in Psychiatry, 2022)
Once a localized Japanese phenomenon, Hikikomori-type social withdrawal has since been observed globally in increasing numbers. However, there is a lack of research about Hikikomori in Singapore. Consequently, local variations of Hikikomori may differ from past research in Japan. Drawing on associations found in international and Japanese Hikikomori research, we explored some variables relevant and generalizable to the Singaporean context. Specifically, we examined the relationships between (1) Hikikomori risk factors, (2) social withdrawal tendencies, (3) depression and anxiety, (4) connections with family and friends, and (5) employment status. In a cross-sectional survey study (N = 416; Mage = 24.90, SDage = 4.79; females = 236, males = 177, undisclosed = 3), we found that (a) Hikikomori risk factors positively correlated with social withdrawal tendencies and depression and anxiety, but negatively correlated with support from family and friends, (b) high Hikikomori risk factors predicted high social withdrawal tendencies, (c) support from friends (one of the psychosocial factors) predicted social withdrawal tendencies together with the Hikikomori risk factors, and (d) social withdrawal tendencies moderated the relationship between Hikikomori risk factors and depression among the emerging adults in Singapore. The current research findings serve as a basis for future Hikikomori research in Singapore.